Brain Epitranscriptomic Analysis Revealed Altered A-to-I RNA Editing in Septic Patients - Zhang, Jing-Qian; Pan, Jia-Qi; Wei, Zhi-Yuan; Ren, Chun-Yan; Ru, Fu-Xia; Xia, Shou-Yue; He, Yu-Shan; Lin, Kaisheng; Chen, Jian-Huan (Frontiers in Genetics, 2022)
Recent studies suggest that RNA editing is associated with impaired brain function and neurological and psychiatric disorders. However, the role of A-to-I RNA editing during sepsis-associated encephalopathy (SAE) remains unclear. In this study, we analyzed adenosine-to-inosine (A-to-I) RNA editing in postmortem brain tissues from septic patients and controls. A total of 3024 high-confidence A-to-I RNA editing events. In sepsis, there were fewer A-to-I RNA editing genes and editing sites than in controls. Among all A-to-I RNA editing sites, 42 genes showed significantly differential RNA editing, with 23 down-regulated and 19 up-regulated in sepsis compared to controls. Notably, more than 50% of these genes were highly expressed in the brain and potentially related to neurological diseases. Notably, cis-regulatory analysis showed that the level of RNA editing in six differentially edited genes was significantly correlated with the gene expression, including HAUS Augmin Like Complex Subunit 2 (HAUS2), Protein Phosphatase 3 Catalytic Subunit Beta (PPP3CB), Hook Microtubule Tethering Protein 3 (HOOK3), CUB and Sushi Multiple Domains 1 (CSMD1), Methyltransferase Like 7A (METTL7A) and Kinesin Light Chain 2 (KLC2). Furthermore, enrichment analysis showed that fewer gene functions and KEGG pathways were enriched by edited genes in sepsis compared to controls. These results revealed alteration of A-to-I RNA editing in the human brain associated with sepsis, thus providing an important basis for understanding its neuropathology in SAE.